Interpretation of Figurative Meanings in Uzbek Proverbs with the "Hospitality" Concept - Shohista Eshankulova (International Journal Of Literature And Languages, 2026)
The national values, traditions, customs, and social environment of every nation are vividly expressed in its oral folklore. This is because a nation's oral folklore not only displays its social values, but also artistically and logically reflects its culture, origins, way of life, psyche, and consciousness. Proverbs, in particular, are monuments that reflect the wisdom of the people and their national traditions and customs. One of the most ancient and enduring values of the Uzbek people is hospitality, which is considered a fundamental element of their social experience, worldview, national culture, and moral norms. In proverbs, this concept is expressed not only directly but also through figurative meanings. The purpose of this research is to identify the semantic and pragmatic features of the concept of hospitality in Uzbek proverbs and to demonstrate how they are interpreted through figurative language.